2021
DOI: 10.3390/brainsci11080990
|View full text |Cite
|
Sign up to set email alerts
|

Dyslexics’ Fragile Oculomotor Control Is Further Destabilized by Increased Text Difficulty

Abstract: Dyslexic adolescents demonstrate deficits in word decoding, recognition, and oculomotor coordination as compared to healthy controls. Our lab recently showed intrinsic deficits in large saccades and vergence movements with a Remobi device independent from reading. This shed new light on the field of dyslexia, as it has been debated in the literature whether the deficits in eye movements are a cause or consequence of reading difficulty. The present study investigates how these oculomotor problems are compensate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 37 publications
5
15
0
1
Order By: Relevance
“…While viewing all three paintings, dyslexics demonstrated uncoordinated eye movements that were similar to those that they made while reading, or while making saccades or vergence movements to audiovisual targets, indicating that their eye movement deficits persist while viewing artwork. Specifically, they demonstrated similar abnormal velocity profiles to those seen while making vergence and saccades to audiovisual targets and while reading, i.e., a faster peak velocity, yet a slower average velocity with a significantly longer duration and a slightly smaller amplitude, suggesting a long deceleration tail that has been discussed in previous studies [12,21]. This observation suggests that abnormalities in the velocity profile of eye movements persist while viewing paintings.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…While viewing all three paintings, dyslexics demonstrated uncoordinated eye movements that were similar to those that they made while reading, or while making saccades or vergence movements to audiovisual targets, indicating that their eye movement deficits persist while viewing artwork. Specifically, they demonstrated similar abnormal velocity profiles to those seen while making vergence and saccades to audiovisual targets and while reading, i.e., a faster peak velocity, yet a slower average velocity with a significantly longer duration and a slightly smaller amplitude, suggesting a long deceleration tail that has been discussed in previous studies [12,21]. This observation suggests that abnormalities in the velocity profile of eye movements persist while viewing paintings.…”
Section: Discussionsupporting
confidence: 75%
“…For all three paintings, dyslexics demonstrated a higher duration, a faster peak velocity, and a higher average velocity in saccades made to the left and right while viewing (see Tables 1-3). This oculomotor profile is similar to that found in dyslexics while reading and while making saccades to audiovisual targets [12,21]. For all three paintings, dyslexics demonstrated a lower amplitude while making saccades to the left.…”
Section: Eye Movement Differences Between Groups By Paintingsupporting
confidence: 79%
See 2 more Smart Citations
“…Though there have only been a few studies in the dyslexic population that have demonstrated deficits in eye movements to random targets that stimulate vergence or saccades independent from reading, such studies are essential to assess the existence of eye movement problems per se. For instance, in the dyslexic population, eye movement abnormalities in vergence have been reported using clinical subjective tests since 1988 and in binocular coordination of saccades to LED targets [1][2][3][4][5]. Most recently, Ward and Kapoula conducted a complete study of large saccades and vergence eye movements in depth using LED targets [6].…”
Section: Introductionmentioning
confidence: 99%